Evaluación de un programa de formación de profesores de matemáticas de secundaria y media: prácticas de planificación e implementación (2020)
Evaluating teacher training programs is important because it allows, among other things, to appreciate the relevance of the design and implementation of the programs to the training needs and to assess whether the expected changes in the curricular practices of the participants have been achieved. The focus of this doctoral thesis is the evaluation of a training program for high school mathematics teachers that participated in the public policy of teacher training in Colombia: Master's in Mathematics Education, of Universidad de los Andes. For this purpose, the thesis was organized into five articles. In these articles I characterize the teachers participating in the training program from their practices of planning and implementation of the mathematics curriculum, I compare their curricular practices of planning, implementation and evaluation before and after participating in the program, I formulate a decision-making model of the professor and presented evidence of the operation of the decision-making model...